A fluorescent microbead-based microfluidic immunoassay chip for immune cell cytokine secretion quantification. Issue 3 (12th January 2018) - Cui, Xin; Liu, Ya; Hu, Dinglong; Qian, Weiyi; Tin, Chung; Sun, Dong; Chen, Weiqiang; Lam, Raymond H. W.
Abstract : Quantitative and dynamic analyses of immune cell secretory cytokines are essential for precise determination and characterization of the "immune phenotype" of patients for clinical diagnosis and treatment of immune-related diseases. Abstract : Quantitative and dynamic analyses of immune cell secretory cytokines are essential for precise determination and characterization of the "immune phenotype" of patients for clinical diagnosis and treatment of immune-related diseases. Although multiple methods including the enzyme-linked immunosorbent assay (ELISA) have been applied for cytokine detection, such measurements remain very challenging in real-time, high-throughput, and high-sensitivity immune cell analysis. In this paper, we report a highly integrated microfluidic device that allows for on-chip isolation, culture, and stimulation, as well as sensitive and dynamic cytokine profiling of immune cells. Such a microfluidic sensing chip is integrated with cytometric fluorescent microbeads for real-time and multiplexed monitoring of immune cell cytokine secretion dynamics, consuming a relatively small extracted sample volume (160 nl) without interrupting the immune cell culture. Furthermore, it is integrated with a Taylor dispersion-based mixing unit in each detection chamber that shortens the immunoassay period down to less than 30 minutes. We demonstrate the profiling of multiple pro-inflammatory cytokine secretions ( e.g. interleukin-6, interleukin-8, and tumor necrosis factors) of human peripheral blood mononuclear cells (PBMCs) with a sensitivity of 20 pg ml −1 and a sample volume of 160 nl per detection. Further applications of this automated, rapid, and high-throughput microfluidic immunophenotyping platform can help unleash the mechanisms of systemic immune responses, and enable efficient assessments of the pathologic immune status for clinical diagnosis and immune therapy.